2011
DOI: 10.4137/bmi.s8326
|View full text |Cite
|
Sign up to set email alerts
|

Detection of suPAR in the Saliva of Healthy Young Adults: Comparison with Plasma Levels

Abstract: The soluble urokinase plasminogen activator receptor (suPAR) has been detected in blood, plasma, serum, urine, ovarian cystic fluid, and cerebrospinal fluid. Elevated suPAR levels in plasma have been associated with negative outcomes in various diseases, such as bacteremia, sepsis, SIRS, cardiovascular disease, cancer, and tuberculosis. The primary aim of this study was to investigate whether suPAR can be detected in saliva from healthy individuals and thus, if saliva suPAR can be related to plasma suPAR, CRP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 22 publications
4
39
3
Order By: Relevance
“…Literature on variation by sex in serum suPAR levels is limited mostly to homogenous northern European populations, and contrary to our findings, demonstrated that suPAR levels are higher in female patients than in male patients (27,30,31). Again, the discrepancy in our findings may be explained by the age ranges of our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Literature on variation by sex in serum suPAR levels is limited mostly to homogenous northern European populations, and contrary to our findings, demonstrated that suPAR levels are higher in female patients than in male patients (27,30,31). Again, the discrepancy in our findings may be explained by the age ranges of our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…6 The circulating form is produced by cleavage of membrane-bound urokinase-type plasminogen activator receptor and is readily detected in plasma, serum, urine, and other bodily fluids. 911 Elevated suPAR levels have been associated with poor outcomes in various patient populations. 1220 In addition, suPAR has been implicated in the pathogenesis of kidney disease, specifically focal segmental glomerulosclerosis and diabetic nephropathy, through interference with podocyte migration and apoptosis.…”
mentioning
confidence: 99%
“…Several studies report lack of differences in suPAR levels between FSGS and other kidney diseases and suggests rather a reduced glomerular filtration as a major cause of increased suPAR in patients with renal disorders [64][65][66][67][68][69]. suPAR is readily detected in both plasma and serum [50,70] and it is also found in urine [50], cerebrospinal fluid [71] and saliva [72]. Blood levels of suPAR are dependent on age and sex [7] with slightly increased levels in elderly and females.…”
Section: Supar As a Clinical Marker Of Inflammation And Organ Damagementioning
confidence: 99%